ASSESSING THE EARLY HOLOCENE ENVIRONMENT OF NORTHWESTERN GUYANA: AN ISOTOPIC ANALYSIS OF HUMAN AND FAUNAL REMAINS. Issue 2 (5th April 2018) - Daggers, Louisa; Plew, Mark G.; Edwards, Alex; Evans, Samantha; Trayler, Robin B.
Abstract : This study uses stable carbon δ 13 C and oxygen δ 18 O isotope compositions data to assess the extent to which diet breadths of northwestern Guyana changed during the Holocene. We analyzed human bone and enamel remains from seven shell mound sites dating between 7500 and 2600 BP. Our analyses demonstrate some constancy in C3 plant availability during the past several thousand years, though we note increasing reliance on such plants beginning in the Early Holocene. We also document warming intervals during the Early Holocene (Early Archaic) that appear to correlate with dry periods known elsewhere in the central Amazon during this period. Abstract : Esta investigación utiliza datos de isótopos estables de carbono δ 13 C y oxígeno δ 18 O para evaluar en qué medida cambió la amplitud de la dieta del noroeste de Guyana durante el Holoceno. Analizamos restos óseos humanos y esmalte de siete concheros fechados entre 7500 y 2600 años aP. Nuestros análisis muestran cierto grado de constancia en la disponibilidad de plantas C3 durante los últimos miles de años, aunque se observa una creciente dependencia en tales plantas a comienzos del Holoceno temprano. También documentamos intervalos más cálidos durante el Holoceno temprano (Arcaico Temprano) que parecen correlacionarse con los periodos secos conocidos en otras partes del Amazonas central durante este lapso.